Handbook of Industrial Chemistry and Biotechnology - Kent, James A.; Bommaraju, Tilak V.; Barnicki, Scott D.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This widely respected and frequently consulted reference work provides a wealth of information and guidance on industrial chemistry and biotechnology. Industries covered span the spectrum from salt and soda ash to advanced dyes chemistry, the nuclear industry, the rapidly evolving biotechnology industry, and, most recently, electrochemical energy storage devices and fuel cell science and technology. Other topics of surpassing interest to the world at large are covered in chapters on fertilizers and food production, pesticide manufacture and use, and the principles of sustainable chemical practice, referred to as green chemistry. Finally, considerable space and attention in the Handbook are devoted to the subjects of safety and emergency preparedness. It is worth noting that virtually all of the chapters are written by individuals who are embedded in the industries whereof they write so knowledgeably.
Industrial Chemistry: What it is and its Role in the World Economy -- Petroleum and its Products -- Coal Technology for Power, Liquid Fuels and Chemicals -- Natural Gas -- Wood and Wood Products -- Biomass Conversion -- Chemistry of Synthetic Organic Chemicals -- Chemistry in the Pharmaceutical Industry -- Dye Application, Manufacture of Dye Intermediates and Dyes -- Chemistry of Structural Adhesives: Epoxy, Urethane and Acrylic Adhesives -- The Agrochemical Industry -- Fertilizers and Food Production -- Pigments, Paints, Polymer Coatings, Lacquers and Inks -- Animal and Vegetable Fats, Oils and Waxes -- Sugar and Other Sweeteners -- Soap, Fatty Acids, and Synthetic Detergents -- Chemical Explosives -- The Nuclear Industry -- Synthetic Nitrogen Products -- Phosphorus and Phosphates -- Sulfur and Sulfuric Acid -- Salt, Chlor-Alkali and Related Heavy Chemicals -- Industrial Gases -- Manufactured Textile Fibers -- Synthetic Resins and Plastics -- Rubber -- Industrial Biotechnology: Discovery to Delivery -- Industrial Enzymes and Biocatalysis -- Industrial Production of Therapeutic Proteins: Cell -- Lines, Culture,Purification -- Nanotechnology: Fundamentals, Principles, Application -- Nanostructured Materials: Industrial Applications -- Electrochemical Energy Storage: Applications, Processes, Trends -- Safety Consideration in the Chemical Process Industry -- Managing an Emergency Preparedness Program -- Applied Statistical Methods in the Chemicals Industry -- Green Engineering -- Industrial Catalysis: A Practical Guide -- Process Control in the Chemical Industry -- Environmental Chemical Determinations -- Energy Usage and Conservation in the Chemical Industry -- Equipment for Chemical Processing Operations -- .
Keywords: Chemistry, Technical; Biotechnology; Electric power production; Pollution; Polymers; Industrial Chemistry; Biotechnology; Electrical Power Engineering; Mechanical Power Engineering; Pollution; Polymers